KEMAMPUAN KEUANGAN DAERAH DAN KESERASIANNYA TERHADAP PERTUMBUHAN EKONOMIKABUPATEN/KOTA DI PROVINSI KALIMANTAN BARAT - B2053151021, MARINTAN KATRINE ELIANA SIRAIT (Jurnal Ekonomi Daerah (JEDA), 2017)
The title of this thesis is â€œCapability of Regional Finance and Its Steadiness towards Economic Growth within the Regencies / Cities of West Kalimantan Province in the Years from 2011 to 2015â€. This research is conducted in the regencies/cities of West Kalimantan Province including twelve regencies and two cities within five years from 2011 to 2015. The issues of this research are: does the capability of regional finance influence the economic growth, does the steadiness ratio of development expenditures influence the economic growth, and does the steadiness ratio of routine expenditures influence the economic growth. The purposes of this research are to test the capability of regional finance which is represented by the variable of regional tax towards the economic growth, to test the steadiness ratio between the development expenditures and the economic growth, and the steadiness ratio between the routine expenditures and the economic growth within the regencies/cities. This research used the analysis instrument of the double-regression analysis by using Eviews 7 application program. The results obtained from the double-regression analysis towards regional tax, the steadiness ratio of development expenditures and the ratio of routine expenditures towards economic growth show that the regional tax gives negative influence insignificantly towards economic growth, meanwhile the steadiness ratio of development expenditures gives positive influence significantly towards the economic growth, and additionally, the ratio of routine expenditures gives positive influence insignificatnly towards the economic growth. Key words: Regional finance, Steadiness ratio, Economic growth